Cost-Effectiveness Analysis of Amlodipine–Candesartan and Amlodipine–Furosemide in Hypertensive Inpatients at RSUD Dr. Loekmono Hadi Kudus, 2023 - Yulia Pratiwi; Mutia Arum Masitoh; Annis Rahmawaty; Mersi Riyanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Hypertension is a major public health problem and a leading risk factor for cardiovascular morbidity and mortality. In hospitalized patients, combination antihypertensive therapy is frequently used to achieve optimal blood pressure control, which may lead to increased healthcare costs. Therefore, evaluating the cost-effectiveness of commonly used antihypertensive combinations is essential to support rational drug selection in hospital settings.Objectives: This study aims to analyze the cost-effectiveness of amlodipine–candesartan and amlodipine–furosemide combination therapies for inpatient hypertension treatment at RSUD dr. Loekmono Hadi Kudus in 2023.Methods: This non-experimental, descriptive study employed a retrospective design using medical record and cost data from 88 hypertensive inpatients. Patient characteristics, length of hospital stay, therapeutic effectiveness, and direct medical costs were analyzed. Therapeutic effectiveness was defined as the proportion of patients achieving target blood pressure based on JNC VIII guidelines. Cost-effectiveness was assessed using the Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER).Results: The amlodipine–candesartan combination demonstrated a lower ACER (Rp48,229 per 1% effectiveness) than amlodipine–furosemide (Rp90,275). The ICER value (−Rp597,651) indicated that amlodipine–candesartan was both more effective and less costly. Higher costs in the amlodipine–furosemide group were associated with injectable drug use and a greater proportion of prolonged hospital stays.Conclusion: Amlodipine–candesartan was more cost-effective than amlodipine–furosemide for managing hypertensive inpatients. These findings support the preferential use of amlodipine–candesartan when clinically appropriate to optimize both clinical outcomes and healthcare resource utilization.